Korona królewska w herbie Skwierzyny = Royal crown in the Skwierzyna coat of arms - Strzyżewski, Wojciech (1960- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Located on the western border of the former Polish-Lithuanian Commonwealth, Skwierzyna for centuries had the status of a royal city. External symbols of the cities` royal status were images of crowns placed on shields of their coats of arms. This very phenomenon was particularly noticeable in the 17th century after the Polish-Swedish war that had ended in 1660.
Keywords: heraldyka miejska; herb miejski; pieczęć miejska; Skwierzyna; civic heraldry; city coat of arms; city seal